2009
DOI: 10.1007/s12199-009-0123-8
|View full text |Cite
|
Sign up to set email alerts
|

Uterotrophic effects of cow milk in immature ovariectomized Sprague–Dawley rats

Abstract: Objectives Milk contains considerable quantities of estrogens and progesterone and as such may be one of the risk factors for hormone-related cancers. To determine the hormonal effects of commercial and traditional types of milk, we performed uterotrophic tests. Methods Forty-five rats were ovariectomized and divided into three groups of 15 animals each. The animals were kept for 7 days on powdered chow and one of three different liquids: commercial milk (C), traditional milk (T), or water. At autopsy, wet and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 39 publications
1
20
2
Order By: Relevance
“…Other reports have been published on estrogenic activity in milk (Zhou et al, 2010). Zhou et al (2010) also used Sprague-Dawley rats; however, they used ovariectomized, immature rats. These animals were exposed to powdered chow and milk for 7 d and used a negative control group that received powdered chow and water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reports have been published on estrogenic activity in milk (Zhou et al, 2010). Zhou et al (2010) also used Sprague-Dawley rats; however, they used ovariectomized, immature rats. These animals were exposed to powdered chow and milk for 7 d and used a negative control group that received powdered chow and water.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the smaller, younger rat model used, it is not unexpected. Unfortunately, no estrogentreated group was included in the Zhou et al (2010) study.…”
Section: Discussionmentioning
confidence: 99%
“…Also, studies on animal models that deal with the impact of hormones in milk on health disorders are contradictory. Zhou et al [25] and Ganmaa et al [62] reported uterotrophic effects of milk feeding in ovariectomized immature rats.…”
Section: Hormones In Food Of Animal Origin and Consumers' Healthmentioning
confidence: 99%
“…Malekeinejad et al (2006) measured 8.2 -20 pg mL -1 of E1 and 10.3 -20.6 pg mL -1 of E2 in milk, and they also found a correlation between milk fat content and concentrations of estrogens. In another study, commercial milk E1 and E2 concentrations were reported to be 150 and 34 pg mL -1 , respectively (Zhou et al, 2010). In dairy products, P4 concentrations also correlated with milk fat content and were found to be, on average, 12 ng mL -1 in whole milk (Malekinejad and Rezabakhsh, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…Some studies suggest that consumption of milk and thus exposure to cows' estrogens might be involved in reproductive and developmental disorders and in increased incidence of hormone related cancers in humans (Maruyama et al, 2010;Ganmaa et al, 2005;Ganmaa et al, 2001;Sharp and Skakkbeak, 1993). Additionally, milk P4 might have an uterotrophic effect in experimental animals (Zhou et al, 2010). However, other studies failed to demonstrate the connection between milk consumption and endocrine disruption (Grgurevič et al, 2016;Larsson et al, 2015;Davoodi et al, 2013;Ganmaa et al, 2004).…”
Section: Introductionmentioning
confidence: 99%